Analysis of Selected Soil Properties in Relation to Soil and Water Conservation Practices in Sibiya Arera, Soro District, South Central Ethiopia - Belayneh Bufebo; Getachew Beyene; Temesgen Addise (The Scientific World Journal)
Soil erosion by water is a severe and continuous ecological problem in the south central highlands of Ethiopia. Limited use of soil and water conservation technologies by farmers is one of the major causes that have resulted in accelerated soil erosion. Within this context, significant attention has been given to soil and water conservation practices. This study was conducted to investigate the effects of soil and water conservation practices on soil physicochemical properties after being practiced continuously for up to 10 years. The physicochemical properties of soil of landscape with physical soil and water conservation structures without biological conservation measures and physical soil and water conservation structures combined with biological conservation measures were compared with soil of landscape without soil and water conservation practices. The result of analysis disclosed that soil and water conservation interventions (both with biological and without biological measures) significantly increased the soil pH, soil organic carbon, total nitrogen, and available phosphorus content than the soil of landscape without soil and water conservation practices. The results of the analysis also showed that the mean value of cation exchange capacity and exchangeable bases (K+, Na+, Ca2+, and Mg2+) of the soil under nonconserved farm field was significantly lower as compared to the soil of adequately managed farm fields. The findings of this study clarified that there was significant variation in soil properties. This variation could be due to uneven transport of soil particles by runoff. Therefore, soil conservation structures supported with biological measures improves the soil’s physicochemical properties.